2020
DOI: 10.47536/jcrm.v21i1.190
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean diversity of Mauritius

Abstract: There is limited information concerning the cetaceans inhabiting the coastal waters of Mauritius.  This document details the sightings of cetaceans encountered during April 2008 – September 2014. Boat-based surveys were conducted throughout the year, primarily focusing on spinner and bottlenose dolphin populations that are important for the local dolphin-watching industry.  More than 1246 hours over 749 days of surveys were spent searching for cetaceans.  All cetaceans encountered were recorded. During 2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…In addition, an individual seen in the Red Sea, to 26°N in September and October 2016, was thought likely to be a SWIOHW, based on the extent of its white pigmentation (Notarbartolo di Sciara et al, 2017). We also note that the seasonality of occurrence in the central Indian Ocean (with just a few individuals recorded in June, a peak in August-September and none after October) closely matches the seasonality of occurrence of SWIOHW wintering within the southwest Indian Ocean (Braulik and Stern, 2020;Dulau-Drouot et al, 2012;Trudelle et al, 2018;Webster et al, 2020) as does the seasonality of calf occurrence.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, an individual seen in the Red Sea, to 26°N in September and October 2016, was thought likely to be a SWIOHW, based on the extent of its white pigmentation (Notarbartolo di Sciara et al, 2017). We also note that the seasonality of occurrence in the central Indian Ocean (with just a few individuals recorded in June, a peak in August-September and none after October) closely matches the seasonality of occurrence of SWIOHW wintering within the southwest Indian Ocean (Braulik and Stern, 2020;Dulau-Drouot et al, 2012;Trudelle et al, 2018;Webster et al, 2020) as does the seasonality of calf occurrence.…”
Section: Discussionsupporting
confidence: 72%
“…Southern right whale strandings were exclusively reported in South Africa and thus reflect the documented distribution of the species Best, 2004a, 2004b). Sperm whale strandings occurred in all countries/territories included in this study and closely correspond to previously reported sightings for this species (e.g., Berggren, 2000;Kiszka et al, 2006;Dulau et al, 2008;Webster et al, 2020;Cerchio et al, 2022). All sperm whale strandings were single individuals and occurred in every season.…”
Section: Analyses By Speciessupporting
confidence: 87%
“…Temporal factors (e.g., breeding season, residency patterns, etc.) and anthropogenic pressures may partially explain the pattern of stranding events reported here (Jackson et al, 2015;Webster et al, 2020;Dudhat et al, 2022;Piwetz et al, 2022;Russell et al, 2022). The seasonal analysis revealed that strandings occur throughout the year, but the stranding peaks differed between mysticetes and odontocetes.…”
Section: Spatiotemporal Patternsmentioning
confidence: 49%
See 1 more Smart Citation